An evaluation of a new single‐use flexible bronchoscope with a large suction channel: reliability of bronchoalveolar lavage in ventilated piglets and initial clinical experience. (28th April 2014) - Mankikian, J.; Ehrmann, S.; Guilleminault, L.; Le Fol, T.; Barc, C.; Ferrandière, M.; Boulain, T.; Dequin, P. F.; Guillon, A.
Summary A single‐use flexible bronchoscope with a large suction channel has become available recently and we have evaluated this innovative device. Firstly, bronchoalveolar lavage was performed and quantified in ventilated piglets. Next, the bronchoscope was evaluated in three intensive care units and a satisfaction questionnaire was carried out. Sixteen bronchoalveolar lavages were performed in piglets with a recovery rate of 83 (79–86 [72–89])% of the instilled volume. Quality and performance of all devices tested was identical. The medical satisfaction questionnaire was as follows: 'acceptable' to 'very good' for quality of aspiration, manoeuvrability and quality of vision; 'very good' to 'perfect' for setting up and insertion. This encouraging preliminary evaluation demonstrates the effectiveness of this new single‐use device, which may obviate the need for disinfection procedures and, thereby, eradicate a potential vector of patient cross‐contamination.